2008
DOI: 10.1016/j.jde.2008.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Instability of equilibrium points of some Lagrangian systems

Abstract: In this work we show that, if L is a natural Lagrangian system such that the k-jet of the potential energy ensures it does not have a minimum at the equilibrium and such that its Hessian has rank at least n − 2, then there is an asymptotic trajectory to the associated equilibrium point and so the equilibrium is unstable. This applies, in particular, to analytic potentials with a saddle point and a Hessian with at most 2 null eigenvalues.The result is proven for Lagrangians in a specific form, and we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…, q n ), where 0 ≤ r < n, π s is an homogeneous polynomial of degree s ≥ 2 which does not have a minimum at the origin, and R obeys lim q→0 R(q) q s = 0. Other relevant works on this conjecture were made by Freire, Garcia and Tal in [2,7], in the first of these articles the conjecture is proved in the case of systems with two degrees of freedom, the second one studies the general case n degrees of freedom and it is shown that if the punctual jet of order s of at 0, j s , shows that have not minimum at origin and the Hessian of in 0 is a positive semi-definite quadratic form whose kernel has dimension at most 2, we have the instability of the origin.…”
Section: Introductionmentioning
confidence: 89%
“…, q n ), where 0 ≤ r < n, π s is an homogeneous polynomial of degree s ≥ 2 which does not have a minimum at the origin, and R obeys lim q→0 R(q) q s = 0. Other relevant works on this conjecture were made by Freire, Garcia and Tal in [2,7], in the first of these articles the conjecture is proved in the case of systems with two degrees of freedom, the second one studies the general case n degrees of freedom and it is shown that if the punctual jet of order s of at 0, j s , shows that have not minimum at origin and the Hessian of in 0 is a positive semi-definite quadratic form whose kernel has dimension at most 2, we have the instability of the origin.…”
Section: Introductionmentioning
confidence: 89%
“…Taliaferro [3] proved that all weak and strong maximum points are unstable if H ∈ C 1 and Palamodov [4] proved that non-minimum points are unstable under the hypothesis of analyticity. Many other relevant partial results were obtained, a good number assuming non-degeneracy conditions or restrictions to the degrees of freedom (see for instance [5][6][7][8]). A common point to these results is that the instability of the equilibrium is proved using different hypothesis on the potential energy but no non-standard hypothesis on the kinetic energy.…”
mentioning
confidence: 99%